AHP model to select suppliers Cloud Computing - Huamaní Huamaní, Gloria Teresita (2014)
In this paper the application of the Analytic Hierarchy Process (AHP) is described, and then the service providers cloud computing is identified. The first activity in multicriteria decision- making is to establish the factors that are important to that decision. This has been determined as criteria in selecting cloud providers: accessibility scalability, performance, security. The SEPROCCAHP v01 model has been applied for three groups of students in the course of business logistics. Two groups of students have selected Google, and a third group at Microsoft. The results differ because it depends on value judgments issued in the peer evaluation criteria and alternatives to select.